Researching children and youth : methodological issues, strategies, and innovations - Castro, Ingrid E.; Swauger, Melissa; Harger, Brent (Sociological studies of children and youth ;, 2017)
Researching Children and Youth: Methodological Issues, Strategies, and Innovations, part of the Sociological Studies of Children and Youth series, seeks to fill a void in current publications directly addressing the problems and pitfalls that often accompany researching children and youth in todays society. Sociologists face increasingly limited access to children and youth given their "vulnerable" status, growing requirements from Institutional Review Boards, and more restricted access from organizations and educational institutions. As a result, researchers must be creative in the pursuit of researching kids and teens. Chapters in this volume address such topics as participatory and feminist ethnographic approaches, digital mining, childrens agency, and navigating IRBs. The importance of contextualizing sociological research with children with special consideration of space, location, and identity thematically runs throughout all of the contributions to this volume.